Emendation and new species of Hapalorhynchus Stunkard, 1922 (Digenea: Schistosomatoidea) from musk turtles (Kinosternidae: Sternotherus) in Alabama and Florida rivers. Issue 6 (December 2017) - Roberts, Jackson R.; Halanych, Kenneth M.; Arias, Cova R.; Folt, Brian; Goessling, Jeffrey M.; Bullard, Stephen A.
Abstract: Hapalorhynchus Stunkard, 1922 is emended based on morphological study of existing museum specimens (type and voucher specimens) and newly-collected specimens infecting musk turtles (Testudines: Kinosternidae: Sternotherus spp.) from rivers in Alabama and Florida (USA). Hapalorhynchus conecuhensis n. sp. is described from an innominate musk turtle, Sternotherus cf. minor, (type host) from Blue Spring (31°5′27.64″N, 86°30′53.21″W; Pensacola Bay Basin, Alabama) and the loggerhead musk turtle, Sternotherus minor (Agassiz, 1857) from the Wacissa River (30°20′24.73″N, 83°59′27.56″W; Apalachee Bay Basin, Florida). It differs from congeners by lacking a body constriction at level of the ventral sucker, paired anterior caeca, and a transverse ovary as well as by having a small ventral sucker, proportionally short posterior caeca, nearly equally-sized anterior and posterior testes, a small cirrus sac, and a uterus extending dorsal to the ovary and the anterior testis. Specimens of Hapalorhynchus reelfooti Byrd, 1939 infected loggerhead musk turtles, stripe-necked musk turtles ( Sternotherus peltifer Smith and Glass, 1947), Eastern musk turtles ( Sternotherus odoratus [Latreille in Sonnini and Latreille, 1801]), and S. cf. minor . Those of Hapalorhynchus cf. stunkardi infected S. minor and S. odoratus . Sternothorus minor, S. peltifer, and S. cf. minor plus S. minor and S. odoratus are new host records for H. reelfooti and H. cf. stunkardi, respectively. This is the first report of an infected musk turtle from the Coosa and Tallapoosa Rivers (Mobile-Tensaw River Basin), Pensacola Bay Basin, or Apalachee Bay Basin. Sequence analysis of the large subunit rDNA (28S) showed a strongly-supported clade for Hapalorhynchus . Graphical abstract: